Little Zion : A Church Baptized by Fire - O'Foran, Shelly (Book collections on Project MUSE., 2006)
One of the churches struck by probable arson in 1996 was Little Zion Baptist Church in Alabama. This book draws on the voices and memories of church members to share a history of Little Zion, from its beginnings as a brush arbor around the time of emancipation, to its key role in the civil rights movement, to its burning and its rebuilding.